The woman they could not silence [compact disc, unabridged] : one woman, her incredible fight for freedom, and the men who tried to make her disappear - Moore, Kate (Writer and editor) (Blackstone, 2021)
From the New York Times, USA Today, and Wall Street Journal best selling author of The Radium Girls comes another dark and dramatic but ultimately uplifting tale of Elizabeth Packard, a forgotten woman whose inspirational journey sparked lasting change for women's rights and exposed injustices that still resonate today.